Menstrual Cycle: Basic Biology - Hawkins, Shannon M. (2008)
The basic biology of the menstrual cycle is a complex, coordinated sequence of events involving the hypothalamus, anterior pituitary, ovary, and endometrium. The menstrual cycle with all its complexities can be easily perturbed by environmental factors such as stress, extreme exercise, eating disorders, and obesity. Furthermore, genetic influences such as fragile X premutations (Chapter X), X chromosome abnormalities (Chapter X), and galactose-1-phosphate uridyltransferase (GALT) point mutations (galactosemia) also contribute to perturbations of the menstrual cycle. Although not perfect, mouse model have helped to identify and confirm additional components and pathways in menstrual cycle function and dysfunction in humans.